Penurunan Kadar BOD dan Amonia dalam Limbah Domestik Dengan Teknologi Fito-Biofilm Menggunakan Tumbuhan Duckweed (Lemna minor) Dengan Media Biofilter Random (studi kasus: Perumahan Graha Mukti, Tlogosari, Semarang) - Risna Damayanti Sihotang (Jurnal Teknik Lingkungan, 2012)
Along with the increasing population growth also resulted in an increase in the amount of waste generated. One of the pollutants contained in domestic sewage are BOD and ammonia content. The technique used is a combination of process phytoremediation, which is using duckweed plants with biofilm formation using a biofilter random. The purpose of this study was to determine the ability of the combined application of fito-biofilm processes in decreasing the levels of BOD and Ammonia in domestic wastewater and the efficiency of decreasing these concentrations. In this study, three reactors are used with the continuous system and varying the time detention in the reactor. The detention time used were 24, 12, 8, 6, 4, and 2 hours. From the results of research conducted, showed that the reduction in BOD and ammonia concentrations reach 99% and 66.61% for BOD and Ammonia. With values ​​for BOD reduction from 180.2 mg / l to 1.81 mg / l and for ammonia, from 5.42 mg / l to 1.81 mg / l.